Influence of mineral and organic fertilization on soil fungi, enzyme activities and humic substances in a long-term field experiment - Rezácová, V; Baldrian, P; Hrselová, H; Larsen, J; Gryndler, M (Folia microbiologica, 2007)
Changes in microfungal communities, fungal activities and humic substances (HS) in agricultural soils kept under different fertilization regimes were observed and their causal relationships were investigated in a long-term field experiment. Fertilization did not change the abundance of HS-utilizing microfungi and, except for organic amendment alone, total culturable microfungi were also unaffected by this factor. Organic fertilization increased activities of manganese peroxidase (MnP) and proteinase, but decreased endo-1,4-beta-glucanase activity compared to the corresponding control without organic fertilization. In soils treated with mineral fertilizers, the activities of MnP, endo-1,4-beta-glucanase and proteinase were higher than in control without any mineral treatment. Both the aromaticity of fulvic acid and the molar mass of humic acid was lower in soil with organic fertilization, which may be a result of oxidative degradation mediated by higher MnP activity observed in treatments with organic fertilization.
Keywords: náhodné rozdělení; Cellulases; benzopyrany; Mitosporic Fungi; mitosporické houby; huminové látky; Peptide Hydrolases; Agriculture; Peroxidases; celulasy; Československo; lakasa; zemědělství; Humic Substances; Hydrogen Peroxide; peroxid vodíku; půdní mikrobiologie; Czechoslovakia; průmyslová hnojiva; Laccase; Fertilizers; peroxidasy; Benzopyrans; Random Allocation; proteasy; Soil Microbiology